Distanciamiento de siembra y su influencia en las características agronómicas y rendimiento de Allium porrum L. "poro", Zungarococha-Loreto. 2019 - Gonzales Cespedes, Brady (2022)
The experiment was carried out in the Teaching and Research Workshop on Horticultural Plants (TEIPH) of the Faculty of Agronomy-UNAP. The research was experimental, explanatory with an independent variable (planting distance) and eight dependent variables (plant height, root length, root weight, number of leaves/plant, bulb diameter, total plant weight, bulb/plant weight and bulb weight/ha); The objective was to determine the influence of planting spacing on the agronomic characteristics and yield of Allium porrum L. "poro". The experimental design was the completely randomized block design, with four treatments and four repetitions. Each experimental unit consisted of 3 rows, 12 plants/row, in T1 (0.20 m. x 0.30 m.); 8 plants/row in T2 (0.30 m. x 0.30 m.); 6 plants/row in T3 (0.40 m. x 0.30 m.) and 5 plants/row in T4 (0.50 m. x 0.30 m.); the sampling unit consisted of three plants/experimental unit. It is concluded that planting spacing significantly influences the agronomic characteristics and yield of Allium porrum L."poro", where Treatment T4 (0.50 m. x 0.30 m.), presented the highest averages in the height characteristics of the plant. plant, number of leaves/plant, bulb diameter. Treatment T2 (0.30 m. x 0.30 m.), presented the best average root length value, with 9 cm. Treatment T3 (0.40 m. x 0.30 m.), had the highest root weight value, with 34 g. Treatment T4, presented the best yield of total weight of the plant, weight of bulb/plant and weight of bulbs/ha. Treatment T4 (0.50 m. x 0.30 m.), presented the best average value of bulb weight/ha, with 12.467 t/ha, followed by T3 (0.40 m. x 0.30 m.), with 8.267 t/ha. ; then T2 (0.30 m x 0.30 m), with 5,000 t/ha and finally T1 (0.20 m x 0.30 m), with 2,000 t/ha; Regarding the Benefit/Cost relationship, the T4 treatment (0.50 m. x 0.30 m.), presented the best economic profitability, with S/.63,520.00.